Perbedaan Kinerja Keuangan PT Ciputra Development Tbk dan PT Pakuwon Jati Tbk Tahun 2019-2023 - Maulana, Julio Ivan; Widuri, Trisnia; Nadhiroh, Umi (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the differences in financial performance between PT Ciputra Development Tbk (CTRA) and PT Pakuwon Jati Tbk (PWON) during 2019–2023 based on liquidity, profitability, solvency, and dividend policy ratios. A quantitative approach with a descriptive-comparative method was employed. The study utilized secondary data obtained from the annual financial reports of both companies listed on the Indonesia Stock Exchange. Financial ratios were analyzed, including the Current Ratio (CR), Return on Assets (ROA), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR). Data normality and homogeneity tests were conducted, followed by Independent Sample t-Test and Mann–Whitney U test using SPSS version 26 to identify statistical differences. The results indicate no significant differences between CTRA and PWON in CR, ROA, and DPR, but a significant difference in DER, where CTRA shows higher leverage compared to PWON. These findings suggest that the key distinction between the two companies lies in their capital structure rather than profitability or dividend policy, reflecting different financial management strategies within Indonesia’s property sector.